You are on page 1of 8

f(x)= x - 3 f(x)= 5x + 3

-2 7 25 38 8 23 38 53

-1 9 27 46 13 28 43 68

3 13 32 47 18 33 48 78

f(x)= 2x - 3 f(x)= 2x + 1

-1 9 17 41 3 17 45 51

1 11 25 47 5 39 47 61

3 13 37 49 15 41 49 63

f(x)= 3x +1 f(x)= x - 1

4 15 28 46 7 14 21 51

7 19 31 52 8 15 24 56

10 25 34 58 10 18 27 71
f(x)= x + 3 f(x)= x - 6

5 14 25 43 -2 4 16 44

8 16 31 45 1 9 30 50

9 20 33 58 3 12 36 60

f(x)= 2x + 3 f(x)= x - 7

5 17 25 37 -1 14 23 44

7 21 33 41 2 20 40 49

15 23 35 63 8 21 41 53

f(x)= 3x - 2 f(x)= x - 9

1 28 43 61 -2 3 47 64

4 34 46 64 -1 6 57 72

7 37 58 67 1 11 60 81
f(x)= x + 7 f(x)= 3x + 2

9 30 49 80 5 26 44 62

15 37 57 87 11 32 47 71

28 45 72 90 17 38 51 77

f(x)= 2x + 4 f(x)= 3x + 1

6 24 46 74 4 28 46 61

10 28 54 86 10 31 52 76

14 34 66 88 16 34 55 82

f(x)= x - 4 f(x)= 2x - 1

1 31 62 77 3 13 25 47

4 44 67 81 7 19 29 53

27 55 72 86 9 21 35 79
f(x)= x +2 f(x)= x + 4

3 17 32 54 5 21 43 75

6 21 39 71 11 27 54 80

12 25 43 87 16 33 67 86

f(x)= x + 5 f(x)= 2x + 2

6 22 44 67 4 22 38 62

10 27 54 71 6 28 42 74

17 34 60 90 18 32 48 82

f(x)= 2x - 1 f(x)= x + 8

1 11 29 41 9 33 55 76

5 17 35 53 18 44 58 79

9 21 39 89 25 49 63 80
f(x)= 2x - 4 f(x)= x - 5

2 16 38 66 5 28 48 63

6 20 46 74 16 33 53 74

12 26 54 80 22 42 58 85

f(x)= x + 6 f(x)= x + 7

7 35 57 72 8 33 57 75

14 39 61 79 14 42 64 79

28 46 66 87 28 49 68 86

f(x)= x - 2 f(x)= x + 1

2 21 37 60 3 16 43 60

10 28 48 73 6 28 51 61

19 32 53 88 10 39 56 69
f(x)= x + 9 f(x)= 2x + 5

10 31 50 69 7 17 31 65

13 39 59 80 9 23 55 73

20 44 61 89 13 25 63 85

f(x)= 2x - 8 f(x)= 3x - 5

-2 7 25 38 8 23 35 53

-1 15 27 42 13 28 43 68

3 13 32 41 18 33 49 72

f(x)= 2x - 9 f(x)= 6x - 3

-2 3 47 64 1 28 43 60

-1 9 51 72 4 31 46 64

1 11 60 85 7 37 52 67
f(x)= 2x - 7 f(x)= 5x + 3

-1 11 23 44 5 17 25 37

2 20 40 49 7 21 28 39

8 21 41 50 15 23 35 65

f(x)= 2x - 6 f(x)= 4x + 3

-2 4 16 44 5 14 25 43

1 9 25 50 8 16 31 44

3 12 38 60 9 20 33 52

f(x)= 3x +1 f(x)= 5x - 1

4 15 28 46 7 14 21 51

7 14 29 52 9 16 24 56

10 25 34 58 10 18 27 62
f(x)= 4x + 1 f(x)= 3x - 5

3 17 45 51 -1 10 17 41

6 39 47 61 1 11 28 47

12 41 50 63 3 13 37 49

f(x)= 2x - 1 f(x)= 4x + 7

5 26 44 62 9 30 49 80

11 36 49 76 17 37 56 87

17 38 51 77 29 45 72 90

f(x)= 6x + 3 f(x)= 2x + 4

4 28 46 61 6 24 46 74

11 32 52 76 12 29 52 86

15 34 55 82 14 34 66 88